Pengelolaan pembelajaran pendidikan agama islam dengan pemanfaatan teknologi artificial intellegence bagi mahasiswa program studi PAI - Surya Putra, Wiene; Wanda, Karina (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
The study aims to explore and analyze the potential use of AI in improving the effectiveness of the teaching and learning process at the Syekh Abdul Halim Hasan Binjai Institute and the Muhammadiyah University of North Sumatra. The method used is a survey with a questionnaire as a data collection tool. The data analysis technique is carried out quantitatively by calculating the percentage of responses from participants. The subjects of this study were 30 lecturers and a number of students at both institutions. The results of the study showed that 75% of lecturers had a good understanding of AI, and 60% of students showed a high interest in learning about this technology. In addition, 80% of lecturers believed that AI could make teaching materials more interesting and interactive, and students felt the benefits through a richer learning experience. The implication is that to improve the integration of AI in religious education, collaboration between various stakeholders is essential.